2019
DOI: 10.1002/bdd.2179
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of absorption and first‐pass metabolism of GL‐V9, a derivative of wogonin

Abstract: GL-V9, a derivative of wogonin, has potent anti-cancer activity. The absorption and metabolism of this compound have not been investigated systematically. This study aims to illustrate the pharmacokinetic characters of GL-V9 by exploring its metabolic status under different administration routes. To further clarify the absorption mechanism of GL-V9, an in situ single-pass perfusion model and a Caco-2 cell monolayer model were used. Meanwhile, a microsomal incubation system was used to evaluate the enzyme kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Generally, glucuronidation studies of a compound are divided into several aspects [33], including UGT-isoform-specific metabolic fingerprint (GSMF) [34], enzyme kinetics and the evaluation of the importance of glucuronidation in the metabolism of the compounds. Previous studies showed that GL-V9 underwent an extensive metabolism in liver after administration, where it could be catalyzed by a family of UGT [35]. It has been reported that UGT1A1, UGT1A3, UGT1A4 and UGT1A9 genes are widely expressed in human liver [36].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, glucuronidation studies of a compound are divided into several aspects [33], including UGT-isoform-specific metabolic fingerprint (GSMF) [34], enzyme kinetics and the evaluation of the importance of glucuronidation in the metabolism of the compounds. Previous studies showed that GL-V9 underwent an extensive metabolism in liver after administration, where it could be catalyzed by a family of UGT [35]. It has been reported that UGT1A1, UGT1A3, UGT1A4 and UGT1A9 genes are widely expressed in human liver [36].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies on WOG have documented its anticancer activity in CRC via inhibition of c-FLIP protein, Jun and PI3K-Akt and activation of TRAIL-R2 expression (Ding et al, 2012;Huang et al, 2020). In addition, other preclinical studies have also demonstrated the anticancer effect of WOG and its derivative, GL-V9 in CRC (Goh, Lee, & Ong, 2005;Willenberg et al, 2015;Xing et al, 2019b). WOG was found to exert its antiproliferative and proapoptotic activity in CRC cells via deregulation of PI3K/Akt and STAT-3 signaling pathways and activation of caspases-3 and caspase-9 expressions (Tan et al, 2019;Wang et al, 2018a).…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Apart from this, the solid dispersion (SD) strategies were reported to increase the water solubility, dissolution rate, stability, and bioavailability of WOG (Yu, Chang, Kim, Kim, & Choi, 2017a). Moreover, other analogs of WOG, such as wogonoside and nor‐wogonin (N‐WOG), and numerous other WOG‐derived compounds, such as, LW‐213, GL‐V9, DN604, V8, oroxylin‐A, and compound 51, have been found to impart potential therapeutic effects against different types of cancers via modulation of various critical cell signaling pathways (Baek et al, 2018; Chen, Qin, Xu, Gou, & Jin, 2017; Hu et al, 2006; Wang et al, 2019a; Xing et al, 2019b; Yao et al, 2017; Zhang et al, 2014; Zhao et al, 2016a). These findings indicate that WOG‐derived compounds have immense potential and WOG‐based NPs and other formulations might provide a promising way to deliver WOG for more efficient cancer treatment.…”
Section: Wog Sources Chemistry and Biological Activitiesmentioning
confidence: 99%
“…In mice, it has been shown that the C max of baicalein is highest in the stomach, followed by jejunum, ileum, and cecum, and is lowest in the duodenum and colon [16]. GL-V9, a synthetic, non-substituted B-ring flavone investigated for its potential anticancer activities, is absorbed predominantly at the level of the duodenum and jejunum [51].…”
Section: Absorptionmentioning
confidence: 99%
“…The extended first-pass biotransformation of flavonoids, mostly by glucuronidation and sulfation, has been shown to be the primary reason for the meager bioavailability of flavonoids [136]. The synthetic flavone GL-V9 is also well absorbed at the intestinal level in rats, but extensive liver metabolism leads to its reduced systemic exposure [51].…”
Section: Metabolism and Stability To Metabolic Attackmentioning
confidence: 99%